Fucosylated umbilical cord blood hematopoietic stem cell expansion on selectin‐coated scaffolds. Issue 12 (17th May 2019) - Islami, Maryam; Payandeh, Zahra; Dalir Abdolahinia, Elaheh; Saburi, Ehsan; Soleimanifar, Fatemeh; Kehtari, Mousa; Mortazavi, Yousef; Nadri, Samad; Darvish, Maryam
Abstract: Despite the advantages of transplantation of umbilical cord blood's (UCB's) hematopoietic stem cells (uHSCs) for hematologic malignancy treatment, there are two major challenges in using them: (a) Insufficient amount of uHSCs in a UCB unit; (b) a defect in uHSCs homing to bone marrow (BM) due to loose binding of their surface glycan ligands to BM's endothelium selectin receptors. To overcome these limitations, after poly l ‐lactic acid (PLLA) scaffold establishment and incubation of uHSCs with fucosyltransferase‐VI and GDP‐fucose, ex vivo expansion of these cells on selectin‐coated scaffold was done. The characteristics of the cultured fucosylated and nonfucosylated cells on a two‐dimensional culture system, PLLA, and a selectin‐coated scaffold were evaluated by flow cytometry, 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide assay, colony‐forming unit (CFU) assay, and CXCR4 expression at the messenger RNA and protein levels. According to the findings of this study, optimized attachment to the scaffold in scanning electron microscopy micrograph, maximum count of CFU, and the highest 570 nm absorption were observed in fucosylated cells expanded on selectin‐coated scaffolds. Furthermore, real‐time polymerase chain reaction showed the highest expression of the CXCR4 gene, and immunocytochemistry data confirmed that the CXCR4 protein was functional in this group compared with the other groups. Considered together, the results showed that selectin‐coated scaffold could be a supportive structure for fucosylated uHSC expansion and homing by nanotopography. Fucosylated cells placed on the selectin‐coated scaffold serve as a basal surface for cell–cell interaction and more homing potential of uHSCs. Accordingly, this procedure can also be considered as a promising technique for the hematological disorder treatment and tissue engineering applications. Abstract : UCB‐CD133+ cells transplantation is used for the hematological disorder that has challenges.